2019
DOI: 10.1029/2018jd029747
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Extreme Events Over Africa Under 1.5 and 2 °C of Global Warming

Abstract: With anthropogenic global warming, heat‐related extreme events are projected to increase in severity and frequency. Already vulnerable regions like Africa will be hard‐hit. Therefore, such regions could benefit from low global warming levels. Using the Community Earth System Model low warming simulations, we investigate changes in temperature extremes across Africa as a function of global mean temperature in the context of the implications of the Paris Agreement's targets. A significant warming across Africa i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 55 publications
3
29
0
Order By: Relevance
“…Yet like other regions there are clear upward trends in Sahel temperatures (e.g., Guichard 2014;Moron et al 2016) most notably during nighttime. Recent studies showed upward trends in duration, frequency and intensity of heatwave events over the past decades (Fontaine et al 2013;Moron et al 2016;Ceccherini et al 2017;Barbier et al 2017) and future projections also show a growing risk of extreme heat in the region (e.g., Nangombe et al 2019;Rohat et al 2019). However, some contradictory evidence of unchanged frequency exists (Adeniyi and Oyekola 2017), which may be related to the choice of heatwave index.…”
Section: Introductionmentioning
confidence: 99%
“…Yet like other regions there are clear upward trends in Sahel temperatures (e.g., Guichard 2014;Moron et al 2016) most notably during nighttime. Recent studies showed upward trends in duration, frequency and intensity of heatwave events over the past decades (Fontaine et al 2013;Moron et al 2016;Ceccherini et al 2017;Barbier et al 2017) and future projections also show a growing risk of extreme heat in the region (e.g., Nangombe et al 2019;Rohat et al 2019). However, some contradictory evidence of unchanged frequency exists (Adeniyi and Oyekola 2017), which may be related to the choice of heatwave index.…”
Section: Introductionmentioning
confidence: 99%
“…Global and regionally downscaled climate models project near-surface temperatures to increase by around 3-6°C by the end of the twenty-first century (Patricola and Cook 2010;Fontaine et al 2011;Mariotti et al 2011;Diallo et al 2012;Vizy et al 2013;Riede et al 2016). Further, extreme hot days (> 90th percentile of present climate) are expected to be more frequent (Russo et al 2014;Dosio 2017;Weber et al 2018;Nangombe et al 2019;Yapo et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The Paris Agreement set a preferable target to limit global warming to 1.5 C above preindustrial levels (United Nations Framework Convention on Climate Change, 1992), and many studies have projected extreme events in models for this 1.5 C warming level (Li et al, 2019;Zhao and Zhou, 2019). Thus, for the comparison with the historical epoch , the period of 2030-2054 was chosen as the future epoch for the following analysis, during which global warming is likely to reach the 1.5 C level (IPCC SR15, 2018;Nangombe et al, 2019). Figure 4 shows the trend ratios for the three regions and the three indicators under the RCP4.5 and RCP8.5 scenarios.…”
Section: Projection Of Ehd Characteristics Using the Optimum Modelsmentioning
confidence: 99%